First Report of Leaf Blight Caused by Fusarium pernambucanum and Fusarium sulawesiense on Plum in Sichuan, China - Lu, Mengmeng (Plant disease, 2022)
Plum (Prunus salicina Lindl.) is widely cultivated for its rich nutrients and flavor in China. In August 2020, leaf blight symptoms were observed on plum in Meishan, Sichuan, China (N29°24', E104°30'). Irregular brown spots initially appeared on the edge or tip of the leaf, then extended to larger taupe lesions that were surrounded by a chlorotic halo. In the late stage, grey-brown blighted tissue covered the entire leaf causing leaves to wither, curl and abscise. The leaves with blight were collected from three different towns in Meishan where the disease incidence was found on 15-30% of plum plants. The margin of diseased leaves was cut into small pieces (3×3 mm), surface disinfected with 75% ethanol solution for 10 s, 2% NaOCl for 1 min, and rinsed in sterile distilled water three times. Tissue pieces were plated on potato dextrose agar (PDA) and incubated at 25°C. Forty-nine morphologically similar colonies were observed on PDA plates after 3-5 days and three of these (TEY9-1, TEY12-1, TEY15A-1) were selected for intensive study. The colonies produced abundant whitish to yellowish aerial mycelium after 7 days incubation at 25°C in the dark. Macroconidia on carnation leaf agar (CLA) were falcate, hyaline, straight to slightly curved, smooth to slightly rough with 3 to 6 septa, the apical cell was blunt or hooked, and the basal cell was barely notched, 31.6 ± 2.4 μm × 4.7 ± 0.4 μm, 28.9 ± 3.0 μm × 4.5 ± 0.5 μm, 32.5 ± 3.4 μm × 4.5 ± 0.5 for TEY9-1, TEY12-1, TEY15A-1, respectively. Microconidia were hyaline, fusoid or ovoid, nonseptate or one-septate, 14.4 ± 3.9 μm × 4.3 ± 0.6 μm, 13.0 ± 3.0 μm × 4.0 ± 0.4 μm, 11.0 ± 2.4 μm × 3.7 ± 0.5 for TEY9-1, TEY12-1, TEY15A-1, respectively. Genomic DNA was extracted from 7-day-old aerial mycelia of these isolates. The internal transcribed spacer (ITS), translation elongation factor (TEF1), calmodulin (CAM) and partial RNA polymerase second largest subunit (RPB2) were amplified using primers ITS4/ITS1, EF1/EF2, CL1/CL2A, and 5f2/7cr, respectively (White et al. 1990; O'Donnell et al. 2000, 2010). Sequences were deposited in GenBank (ITS: OK315638-OK315640; TEF1: OK338756-OK338758; CAM: OK338759-OK338761; RPB2: OK338762-OK338764). A maximum Likelihood (ML) phylogenetic tree was constructed with RAxML version 8.2.10 based on the concatenated sequences (ITS, TEF1, CAM, RPB2). According to morphology and phylogenetic analysis, TEY9-1 and TEY15A-1 were identified as Fusarium pernambucanum, and TEY12-1 was identified as Fusarium sulawesiense. Pathogenicity tests were conducted on young healthy leaves of 12 two-year-old plum plants in a 28°C greenhouse in Nanning, Guangxi, China. The epidermis of tested leaves was slightly scratched with sterile toothpick-tips forming a 3-mm-diameter cross-shaped wound, followed by inoculation with a 10 μl conidial suspension (106 spores /ml in 0.1% sterile Tween 20). Control leaves were wounded in the same way and treated with 0.1% sterile Tween 20. Plants were covered with polythene bags to maintain high humidity for 5 days. Inoculated leaves showed light brown to dark brown lesions, whereas control leaves were symptomless. Both species were re-isolated from symptomatic leaves, completing Koch's postulates. To our knowledge, this is the first report of F. pernambucanum and F. sulawesiense causing leaf blight on plum trees in China. These results will provide valuable information for prevention and management of leaf blight on plum trees